Experiencing risk: higher-order risk attitudes in description- and experience-based decisions - Becker, Christoph; Ert, Eyal; Trautmann, Stefan T.; Kuilen, Gijs van de (Journal of experimental psychology. Learning, memory, and cognition, 2021)
Risky decisions are often characterized by (a) imprecision about consequences and their likelihoods that can be reduced by information collection, and by (b) unavoidable background risk. This article addresses both aspects by eliciting risk attitude, prudence, and temperance in decisions from description and decisions from experience. The results reveal a novel description-experience gap for prudence and replicate the known gap for risky decisions. While widespread prudence has been observed in decisions form description, we find no evidence of prudent decision making from experience. In decisions from experience people are strongly influenced by the sampled mean, while skewness plays a smaller role than in decisions from description. (PsycInfo Database Record (c) 2021 APA, all rights reserved)